EFFECT OF 7ES INSTRUCTIONAL LEARNING MODEL ON SENIOR SECONDARY STUDENTS’ ACADEMIC ACHIEVEMENT AND RETENTION IN GENETICS IN ZAMFARA STATE, NIGERIA (UNIZIK Journal of STM Education, 2023)
The study aimed to investigate the effect of 7Es instructional learning model on academic achievement and retention in genetics among senior secondary school students in Zamfara State, Nigeria. Four research questions guided the study and four hypotheses were tested. The quasi-experimental research design was adopted for the study, with an experimental group exposed to the 7Es model and a control group taught using the Demonstration method. The population consisted of 18,960 Senior Secondary 3 biology students, with two public senior secondary schools purposively selected. Two intact classes, totaling 120 students, participated - 60 in each group. Data collection used the Genetics Achievement Test (GAT), comprising 30 multiple-choice items. The GAT was validated, and has reliability coefficient of 0.87 was established through the KR-21 formula. Data collected were analyzed using mean, standard deviation for the research questions, and hypotheses were tested using Analysis of Covariance at a 0.05 significance level. The findings of the study reveals that, the 7Es model outperformed the Demonstration method in improving students’ academic achievement. Gender did not significantly affect academic achievement of students taught genetics using 7Es instructional learning model, and also reveals nosignificant difference between the mean retention scores of male and female students. It was recommended among others that; biology teachers should prioritize the use of 7Es model for teaching Genetics over the use of Demonstration method.
Keywords: 7Es instructional model; genetics; academic achievement; retention; students; secondary school